Brássicas e termoterapia no controle de bolor verde de laranja pera em pós-colheita - Koltz, Elizabeth Aparecida (2018)
The green mold caused by the fungus Penicillium digitatum is one of the main diseases of citrus fruits, which causes postharvest losses. The study aimed to evaluate the potential of the canola and mustard compounds in the control of P. digitatum in the postharvest of orange pear. Tests were carried out with different concentrations of powder of each brassica, cultivated and collected, dried in a greenhouse and ground to obtain the powder. In the sachet treatment, the amounts of 6, 12, 18 and 24 g of powder were packed in sachets, moistened and distributed in trays containing the fruits inoculated with the pathogen. The treatment of aqueous extraction modes, in the simple mode, the powder was mixed with water and filtered. For extraction by maceration, the extract was filtered after 8 hours. For infusion extraction, water was heated at 100 ° C and after 20 minutes the solution was filtered. The sachet containing the concentrations of 24 g of powder and the simple aqueous preparation of each plant material were selected to compose combinations of treatments with the thermotherapy by immersion of the fruits in hot water (57 ° C for 60s). The treatments were: 1 - Handmade sachet (S) of canola 24 g or mustard 24 g; 2 - Simple aqueous extract (EAS) of canola or mustard; 3 - Heat treatment + handmade sachet (TTS) of canola 24 g and mustard 24 g; 4 - Thermal treatment associated with the simple aqueous extract (TTE) of canola or mustard; 5 - Heat treatment (TT); 6 - Simple warm aqueous extract of canola or mustard (EA) (57 ° C); 7 - Simple aqueous extract of canola or mustard with posterior inoculation of the pathogen and Thermal treatment (EITT); 8 - Witness (T). The associations with the thermotherapy did not have a greater effect on the inhibition of the pathogen and the best treatments were selected to be compared to the chemical treatment (imazalil 1g a.L / L). The extractive methods tested for the two species of brassicas significantly reduced the mycelial growth and conidia production of P. digitatum in the in vitro tests, as well as the green mold lesion area and the number of conidia in the in vivo tests. The most efficient treatment was with brassica powder in artisanal sachet, reducing the disease by up to 85.0% (canola) and 63.1% (mustard). The use of handmade sachets with brassica powder, such as canola, and simple aqueous extract for ease of application, are presented as efficient alternatives for the control of green mold in post-harvest orange Pera.